Antibiotic Administration Along with Endodontic Therapy in the Republic of Croatia: a Pilot Study - Josipa Sović; Sanja Šegović; Ivan Tomašić; Božidar Pavelić; Ivana Šutej; Ivica Anić (University of Zagreb. School of Dental Medicine, 2020)
Objective: To evaluate the type and the frequency of antibiotic prescribing along with endodontic therapy in Croatia. The aim is, also, to assess the attitudes of Croatian doctors towards endodontic treatment of patients at risk of developing bacterial endocarditis. Material and methods: Data were collected by a survey questionnaire. Results:8.4% of the examined practitioners stated that they prescribe antibiotics often, and 91.6% of them stated that they prescribed them never/ very rarely/rarely. Most of them (41%) prescribe antibiotics once or twice a month, 32.5% once or twice in several months and 20.5% once or twice a week. The most commonly used antibiotic was penicillin with clavulanic acid. Also, 26.2% of examined practitioners prescribed antibiotics for gangrene pulp, 51.2% of them for localized acute apical periodontitis without swelling, 85% of them for cellulitis, 75% of them for fever and enlarged lymph nodes, 16.9% of them for tooth with fistula and 94.1% of them for prophylaxis of infectious endocarditis. According to the results of study, 54.4% of dental practitioners did not prescribe antibiotics without intervention on susceptible tooth; 76% of participants often/almost always/ always accepted endodontic treatment of patients requiring antibiotic prophylaxis to prevent infectious endocarditis, and 96.7% of participants indicated they were familiar with recent instructions for antibiotic prophylaxis. Conclusion: These findings point to inappropriate use of antibiotics in the practice of 83 dental practitioners questioned regarding the frequency of administration and indications. The most commonly used antibiotic was penicillin with clavulanic acid. A high percentage of surveyed practitioners stated that they were familiar with recent instructions for antibiotic prophylaxis. They also stated that they performed endodontic procedures on patients who were at risk of bacterial endocarditis. There is a noticeable need for targeted continuing education of dental practitioners in the Republic of Croatia.